2012
DOI: 10.1371/journal.pone.0041792
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Features of Emotional Expressions Are Processed Preferentially

Abstract: Diagnostic features of emotional expressions are differentially distributed across the face. The current study examined whether these diagnostic features are preferentially attended to even when they are irrelevant for the task at hand or when faces appear at different locations in the visual field. To this aim, fearful, happy and neutral faces were presented to healthy individuals in two experiments while measuring eye movements. In Experiment 1, participants had to accomplish an emotion classification, a gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
114
4
7

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(151 citation statements)
references
References 49 publications
26
114
4
7
Order By: Relevance
“…1B; two-tailed unpaired t test comparing average z scores within the ROIs: for fear-face trials, P = 0.51 for eyes and P = 0.36 for mouth; for happy-face trials, P = 0.68 for eyes and P = 0.14 for mouth], confirming that patients performed the task with a normal strategy. Both patients and controls primarily used information revealed by eyes to judge fear faces, whereas they used more mouth information to judge happy faces, consistent with previous studies (34,35).…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…1B; two-tailed unpaired t test comparing average z scores within the ROIs: for fear-face trials, P = 0.51 for eyes and P = 0.36 for mouth; for happy-face trials, P = 0.68 for eyes and P = 0.14 for mouth], confirming that patients performed the task with a normal strategy. Both patients and controls primarily used information revealed by eyes to judge fear faces, whereas they used more mouth information to judge happy faces, consistent with previous studies (34,35).…”
Section: Resultssupporting
confidence: 86%
“…Behaviorally, our epilepsy patients did not differ from healthy controls in terms of learning performance on the task, and both epilepsy patients and control subjects primarily used the eye region of the stimuli to correctly judge fear faces and primarily used the mouth region to correctly judge happy faces, findings consistent with prior studies (34,35). Forty-one out of 185 cells significantly differentiated the two emotions, and subsequent analyses indicated that these cells encoded the patients' subjective judgment regardless of whether it was correct or incorrect.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Behavioural research presenting face parts (e.g., Calder, Young, Keane, & Dean,2000) or using response classification techniques such as Bubbles (e.g., Blais, Roy, Fiset, Arguin, & Gosselin, 2012;Smith et al, 2005) has highlighted the importance of these so-called "diagnostic features" for the discrimination and categorization of these facial emotions. Eyetracking research also supports the idea that attention is drawn to these features early on, as revealed by spontaneous saccades towards the eyes of fearful faces or the mouth of happy faces presented for as short as 150ms (Gamer, Schmitz, Tittgemeyer, & Schilbach, 2013;Scheller, Büchel, & Gamer, 2012). the most useful diagnostic information for the discrimination of fearful facial expressions and the mouth for the discrimination of happy facial expressions, and that the N170 peaks when these diagnostic features are encoded (Schyns, Petro, & Smith,2007).…”
Section: Role Of Facial Features In the Processing Of Facial Expressionmentioning
confidence: 72%
“…Several psychological studies [14] [9] [13] have demonstrated that humans look at specific locations of the face to identify emotions. These locations present diagnostic information described by features which are important for the analysis of emotional expressions.…”
Section: Mapping Of Emotional Elementsmentioning
confidence: 99%